2019
DOI: 10.1128/mbio.01867-19
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Fungal Type I Myosin in Regulating Membrane Properties and Its Association with d -Amino Acid Utilization in Cryptococcus gattii

Abstract: We found a novel role of Myo5, a type I myosin (myosin-I), and its fortuitous association with d-amino acid utilization in Cryptococcus gattii. Myo5 colocalized with actin cortical patches and was required for endocytosis. Interestingly, the myo5Δ mutant accumulated high levels of d-proline and d-alanine which caused toxicity in C. gattii cells. The myo5Δ mutant also accumulated a large set of substrates, such as membrane-permeant as well as non-membrane-permeant dyes, l-proline, l-alanine, and flucytosine int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…We attempted to test the ortholog of FCY2 from Cryptococcus neoformans using a deletion collection strain but found that the mutant in the collection retained a functional copy of the FCY2 gene. However, fcy2 deletion has recently been reported to confer resistance to 5FC in C. deuterogattii 12 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attempted to test the ortholog of FCY2 from Cryptococcus neoformans using a deletion collection strain but found that the mutant in the collection retained a functional copy of the FCY2 gene. However, fcy2 deletion has recently been reported to confer resistance to 5FC in C. deuterogattii 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, one strain (RBB18-4) that was cross resistant to 5FU had a mutation in the FCY2 gene (CNBG_3227), which in other species confers resistance to 5FC but not 5FU. Mutation of FCY2 is known to result in resistance to 5FC in C. deuterogattii, but cross-resistance to 5FU has not been tested 12 . Unexpected cross-resistance between 5FC and fluconazole has been previously observed in fcy2 mutants of Candida lusitaniae but is proposed to occur through competitive inhibition of fluconazole uptake by 5FC that can no longer enter through Fcy2mediated transport 8,38,39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myosins are actin-dependent molecular motors and play roles in several cellular processes. More specifically, the head myosin domain binds to actin in an ATP-dependent manner and generates force by ATP hydrolysis [63].…”
Section: Identification Of Chs Genes In D Teres and Phylogenetic Anamentioning
confidence: 99%
“…Myosins are actin-dependent molecular motors and play roles in several cellular processes. More specifically, the head myosin domain binds to actin in an ATP-dependent manner and generates force by ATP hydrolysis [63]. CHSs have several conserved domains which are considered as signature sequences since they are found in all CHSs [64].…”
Section: Identification Of Chs Genes In D Teres and Phylogenetic Anamentioning
confidence: 99%